Positioning system of a torch used in thermal spray coatings applications - Torres-Barahona, Edgar Absalón; Moreno-Téllez, Carlos Mauricio; Pinto-Salamanca, María Luisa; Cárdenas, Leydi Julieta; Fuentes-Mojica, Juan David (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2016)
This paper presents the design, construction and performance evaluation of a positioning system used for the deposition of coatings with molten particles, by using a torch CastoDyn Ds 8000 thermal spray with oxyacetylene combustion. The design has been done with parameters obtained in the laboratory of materials of the Universidad Pedagógica y Tecnológica de Colombia, and the information determined from the evaluation of the device, allows to control the main process variables as the projection distance, flow powder, torch speed and rotation speed of the sample holder; this has been seen in coatings made in application tests zirconia / nickel on a carbon steel substrate and analyzed with Scanning Electron Microscopy - SEM.